Variation in compositional and structural components of community assemblage and its determinants. (19th February 2019) - Yao, Jie; Zhang, Chunyu; De Cáceres, Miquel; Legendre, Pierre; Zhao, Xiuhai
Abstract: Questions: What are the ecological processes that determine the spatial distribution of species and species diversity? Partitioning beta diversity can provide fundamental insights into the processes that determine the spatial variation of species assemblages. However, studying beta diversity is conventionally based only on species composition data, ignoring the structural component of communities. Study site: Temperate mixed broadleaf–conifer forest in Jiaohe, Jilin Province, northeastern China. Methods: We characterized the variation of community assemblages in terms of species composition, size structure, or considering both components. We then employed environmental and spatial variables as explanatory factors to partition the variation in both compositional and structural components of community assemblage and assess the relative contributions of the niche and neutral processes to community assembly. Results: The values of overall beta diversity (BD statistics) and the relative contribution of individual sampling units to beta diversity (LCBD indices) depended on whether the species composition, size structure, or both together had been taken into account. The value of compositional–structural beta diversity was the largest, followed by traditional compositional beta diversity; the smallest was the structural beta diversity. The sites with high contributions to beta diversity (LCBD values) varied among structural and compositional components. The explanatory power of the environmental variables and the spatial variables also varied widely with different components of a community. The combination of environmental and spatial variables explained the highest proportion of variation (43.8%) in the compositional component and explained the lowest proportion of variation (25.4%) in the structural component of community assemblage. Conclusion: Both deterministic and stochastic processes are acting to determine community assemblages in terms of species composition and structure in our temperate forest site. Our study highlights the importance of considering the structural component of forest communities, in addition to compositional data, when studying beta diversity. Abstract : A very weak correlation between uniqueness in terms of species composition individually and in terms of size structure individually indicates that sites that are unique in species composition are not necessarily unique in size structure, and vice versa. Considering both species compositional and size structural components may be a more comprehensive way to describe the community organization.